Upaya Meningkatkan Kompetensi Guru melalui Supervisi Pendidikan - Fatimah, Meti; Adin, Ahmad Muchlis; Rahadi, Rahmat; Nasron, Mohammad Alif (TSAQOFAH, 2025)
Teacher competence is one of the key factors influencing the quality of education in a country. Competent teachers are able to carry out the teaching and learning process effectively, enabling students to achieve optimal learning outcomes. However, in reality, not all teachers possess adequate competence. Therefore, continuous efforts are required to improve teacher competence. One effective way to achieve this is through educational supervision. This study aims to identify the definition of teacher competence, understand the role of supervision in improving teacher competence, and explore the strategies of supervision to enhance teacher competence. The research method used is a literature review with a qualitative approach, analyzing various literatures related to educational supervision. Data was collected through a review of relevant journals, articles, and books, and analyzed descriptively. The findings indicate that with effective supervision, teachers can receive the guidance and support needed to develop their professional competence. Several supervision strategies that can be applied include clinical, collaborative, formative, and technology-based supervision. With continuous and directed supervision, it is expected that teacher competence will improve, which in turn will enhance the overall quality of education.